Debt Books and a Book on Debts - Yudin*Greg (Journal of Economic Sociology, 2016)
David Graeber’s Debt is certainly among the most prominent social science books of the last decade. It undertakes a careful analysis of the nature of debt and suggests a new vision of a number of economic and political phenomena — money, exchange, market, state. The research is particularly interesting for shedding a light on the moral foundations of economic behavior. Graeber studies the moral dimension of markets and develops a powerful tool for concrete analysis of contemporary economy in its relation to power, inequality, and international politics. The book takes for its main objective an explanation of why we tend to believe that ‘one has to pay one’s debts’ regardless of circumstances. A historical-anthropological investigation demonstrates that money debts are closely linked to both expansion of markets and strengthening of states. The book is addressed to a wide audience; however, it is also a highly valuable source for anthropologists, sociologists, historians and political philosophers. In the published book review, G. Yudin* continues to discuss Graeber’s monograph.1 He unfolds the key ideas, demonstrates their contributions to research discussions on moral economy, and indicates the strengths and weaknesses of the Russian translation.